Analysis Work Accident of Work Accident of Employee Accident in CV. Pasific Harvest Muncar Banyuwangi District - Hadi Nur Efendi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Occupational accident is one of the most frequent problems with workers in the company. This work accident usually occurs because of the factor of the worker himself and the working environment which in this case is from the employer. The purpose of this study is to analyze the most dominant factors that affect the workplace accident prevention efforts on the occurrence of work accidents in CV. Pacific Harvest Muncar Banyuwangi. The research design used was cross sectional. The research population is All employees in the production department CV. Pacific Harvest of 273 people and a large sample of 162 people. The sampling technique using Simple random sampling and data collection using questionnaire then analyzed using logistic regression. The results showed that there is influence of K3 assurance against work accident (p-value = 0,022 <0,05); there is effect of K3 training to work accident (p-value = 0,039 <0,05); there is influence of APD to work accident (p-value = 0,023 <0,05); no effect of workload on work accident (p-value = 0,938> 0,05); and There is no effect of working hours on work accidents (p-value = 0.699> 0.05). The conclusion is expected for the respondent to pay more attention to health and safety while doing his job because of the many factors that can cause the work accident, the use of personal protective equipment according to the rules and always pay attention to the condition of the field and safe action in work will decrease the risk of accident work.